The complete mitochondrial genome sequence of white-spotted char (Salvelinus leucomaenis). (3rd September 2015) - Zhang, Yong-Quan; Tong, Guang-Xiang; Bai, Qing-Li; Wang, Bing-Qian; Yin, Jia-Sheng
Abstract: The complete sequence of the mitochondrial genome of the white-spotted char ( Salvelinus leucomaenis ) was determined to be 16, 658 bp in length, which contains the control region (CR), the origin of light-strand replication (OL), 22 transfer RNA genes, 2 ribosomal genes and 13 protein-coding genes. Overall, base composition of the complete mitochondrial DNA was 28.20% A, 26.51% T, 28.39% C, 16.90% G, with 54.71% AT.